(untitled) (Journal of Economic Research & Business Administration, 2018)
This work is devoted to liberalization in the sphere of banking services; the study has been carried out to identify the relationship between liberalization and the development of the banking services sector. The works of foreign and domestic scientists on liberalization of services, liberalization of banking services and the development of banking services were studied to explore the influence of liberalization on increasing the availability and reliability of banking services. The scientific significance of this study is an identification of the relationship between liberalization and indicators of reliability and accessibility of banking services. The data obtained during the research can be applied in the deregulation of the sphere of production of services, particularly in banking, and these studies can be used to prepare policies for the development of the services sector. The study used structural-logical analysis to construct logical relationships, as well as empirical analysis to determine the degree of liberalization of banking services in Kazakhstan. Based on the data of rating agencies, the current state of the banking sector of the Republic of Kazakhstan was analyzed on the reliability parameter. The analysis of the impact of such liberalization processes as providing a free currency regime, liberalizing currency operations, eliminating restrictions for foreign banks, and softening requirements for licensing on the reliability and accessibility of banking services was conducted during this research.